Flypaper effect at the local governments: an empirical analysis for Aceh Province - Irham Iskandar (Universitas Islam Indonesia, 2015)
The objective of this reseach is to test the phenomenon of flypaper effect in local governments in Aceh Province during 2008 to 2012. The research used panel data analysis. Technically, it regresses the independent variables of the local owned revenue and unconditional grants on dependent variable of public spending where the institutions as a moderating variable. The flypaper effect was found in the case of public and infrastructure expenditures. The study also found that the institution is capable to reduce the use of unconditional grants. It means that by the role of institution the local owned revenue can be optimized.